Effects of tacrolimus (FK506) and mycophenolate mofetil (MMF) on regulatory T cells and co-inhibitory receptors in the peripheral blood of human liver allograft patients. (4th May 2019) - Zeng, Qiang; Yuan, Xiao-Ye; Li, Wei; Liu, Bao-Wang; Zhao, Xin; Ren, Gui-Jun; Wang, Yang; Dou, Jian; Wang, Gui-Ying
Abstract: Context: Recent studies have shown that a combination treatment of mycophenolate mofetil (MMF) and tacrolimus (FK506) may be an option for organ transplantation patients. Objective: In this study, we detected the effects of FK506 and MMF on the expressions of regulatory T cells (Tregs) and co-inhibitory receptors on Tregs in peripheral blood mononuclear cells (PBMC) of patients with stable phase after liver transplantation. Materials and methods: A total of 35 patients with stable stage after 6 months of liver transplantation were divided into two groups including 20 patients were treated with FK506 monotherapy (FK506 group), and 15 patients with FK506 and MMF combination (FK506 + MMF group). 15 healthy subjects were served as the control. Results: It is found that percentages of CD3 +, CD3 + CD4 + and CD3 + CD8 + T cells in FK506 group are lowered compared to the control group but they are elevated in FK506 + MMF group. Amount of CD4 + CD25 + CD127low/-Treg cells in CD3 + CD4 + T cells in FK506 + MMF group was higher than that in FK506 group and control group. The expressions of co-inhibitory receptors (CTLA-4, PD-1, Tim-3, LAG-3 and TIGIT) on Tregs in FK506 + MMF group were significant higher than those in the FK506 group and control group. The levels of the relative cytokines (TGF-β and IL-10) in FK506 group are down-regulated compared to the control group. Conclusion: The application of FK506 combined with MMF may be superior to FK506 monotherapy for the patients to further induce the immune tolerance after liver transplantation.